In Vivo Evaluation of Active and Passive Physiological Control Systems for Rotary Left and Right Ventricular Assist Devices. Issue 9 (8th January 2016) - Gregory, Shaun D.; Stevens, Michael C.; Pauls, Jo P.; Schummy, Emma; Diab, Sara; Thomson, Bruce; Anderson, Ben; Tansley, Geoff; Salamonsen, Robert; Fraser, John F.; Timms, Daniel
Abstract: Preventing ventricular suction and venous congestion through balancing flow rates and circulatory volumes with dual rotary ventricular assist devices (VADs) configured for biventricular support is clinically challenging due to their low preload and high afterload sensitivities relative to the natural heart. This study presents the in vivo evaluation of several physiological control systems, which aim to prevent ventricular suction and venous congestion. The control systems included a sensor‐based, master/slave (MS) controller that altered left and right VAD speed based on pressure and flow; a sensor‐less compliant inflow cannula (IC), which altered inlet resistance and, therefore, pump flow based on preload; a sensor‐less compliant outflow cannula (OC) on the right VAD, which altered outlet resistance and thus pump flow based on afterload; and a combined controller, which incorporated the MS controller, compliant IC, and compliant OC. Each control system was evaluated in vivo under step increases in systemic (SVR ∼1400–2400 dyne/s/cm 5 ) and pulmonary (PVR ∼200–1000 dyne/s/cm 5 ) vascular resistances in four sheep supported by dual rotary VADs in a biventricular assist configuration. Constant speed support was also evaluated for comparison and resulted in suction events during all resistance increases and pulmonary congestion during SVR increases. The MS controller reduced suction events and prevented congestion through an initial sharp reduction in pump flow followed by a gradual return to baseline (5.0 L/min). The compliant IC prevented suction events; however, reduced pump flows and pulmonary congestion were noted during the SVR increase. The compliant OC maintained pump flow close to baseline (5.0 L/min) and prevented suction and congestion during PVR increases. The combined controller responded similarly to the MS controller to prevent suction and congestion events in all cases while providing a backup system in the event of single controller failure.